Time trends of human papillomavirus types in invasive cervical cancer, from 1940 to 2007. Issue 1 (30th December 2013) - Alemany, Laia; de Sanjosé, Silvia; Tous, Sara; Quint, Wim; Vallejos, Carlos; Shin, Hai‐Rim; Bravo, Luis E.; Alonso, Patricia; Lima, Marcus A.; Guimerà, Núria; Klaustermeier, JoEllen; Llombart‐Bosch, Antonio; et al.
Abstract : Contribution over time of human papillomavirus (HPV) types in human cancers has been poorly documented. Such data is fundamental to measure current HPV vaccines impact in the years to come. We estimated the HPV type‐specific distribution in a large international series of invasive cervical cancer (ICC) over 70 years prior to vaccination. Paraffin embedded ICC cases diagnosed between 1940 and 2007 were retrieved from eleven countries in Central‐South America, Asia and Europe. Included countries reported to have low‐medium cervical cancer screening uptake. Information on age at and year of diagnosis was collected from medical records. After histological confirmation, HPV DNA detection was performed by SPF‐10/DEIA/LiPA25 (version1). Logistic regression models were used for estimating the adjusted relative contributions (RC) of HPV16 and of HPV18 over time. Among 4, 771 HPV DNA positive ICC cases, HPV16 and HPV18 were the two most common HPVs in all the decades with no statistically significant variations of their adjusted‐RC from 1940–59 to 2000–07 (HPV16—from 61.5 to 62.1%, and HPV18—from 6.9 to 7.2%). As well, the RC of other HPV types did not varied over time. In the stratified analysis by histology, HPV16 adjusted‐RC significantly increased across decades in adenocarcinomas. Regarding age, cases associated to either HPV16, 18 or 45 were younger than those with other HPV types in all the evaluated decades. The observed stability on the HPV type distribution predicts a high and stable impact of HPV vaccination in reducing the cervical cancer burden in future vaccinated generations. Abstract : What's new? Evaluation of the success or failure of human papillomavirus (HPV) vaccination programs depends in part on knowledge of the historical contribution of the different HPV types to human cancer. The present study analyzed HPV type‐specific relative contributions to invasive cervical cancer (ICC) over a 70‐year period prior to the implementation of HPV vaccination. The relative contributions of different HPV types, including those for which a vaccine is now available, were found to be constant across decades. The findings indicate that HPV vaccination will have a high, stable impact on cervical cancer reduction.